Artículos sobre Irlanda - Longuet, Jenny Marx, 1844-1883 (Ediciones Godot, 2014)
Articles published in La Marseillaise, in 1870, and writing under the pen name "J. Williams" on the treatment of the Irish political prisoners by the British government.